TANGGUNG JAWAB SUAMI DALAM NAFKAH KELUARGA PERSPEKTIF HADIS - Ansari, Ansari (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2026)
This research is motivated by the importance of a comprehensive understanding of the husband's responsibility in providing for the family as taught in the hadith, in the midst of differences in interpretation and practice in society. The inconsistency of understanding is often influenced by the limitations of the study of the validity and meaning of hadith in depth, both from the aspects of sanad and matan. Therefore, this study aims to examine hadiths related to the husband's maintenance obligation by focusing on validity (validity) and the contextual meaning of its content. The research method used is qualitative with a library research approach, and uses a normative-theological approach and hadith criticism (naqd al-hadith). Data are obtained from primary sources in the form of mu'tabarah hadith books and supported by secondary sources such as sharia books, fiqh books, and scientific journals. The data analysis technique was carried out through takhrij hadith, sanad and matan criticism, and content analysis. The results of the study showed that the hadiths about the husband's maintenance obligation had a strong level of validity and emphasized that the provision of maintenance is the husband's main responsibility which is not only material, but also includes moral and social aspects in family life.